Halloween : Castro 10/90. Source 2 - Kassel, Vampyre Mike; Maschal, Ted, 1960- (San Francisco, CA: Familiar Productions, 1990)
Vampyre Mike and Ted Maschal take to the streets during Halloween in the Castro to interview attendees and join in the celebration. Available on YouTube at https://youtu.be/grw-R3QFgac
Halloween in the Castro (1990)
1 Video DVD-R disk. Digitized: 1 Electronic record(s). MP4. 17.7 GB. 02:04:48.
Keywords: Halloween in the Castro (1990 : Castro, San Francisco, Calif.); Halloween--California--San Francisco; Block parties--California--San Francisco; Gays--California--San Francisco; Gay community--California--San Francisco; Castro (San Francisco, Calif.)--Social life and customs; Familiar Productions (San Francisco, Calif.); Unedited footage; Video recordings